\(\left(x+3\right)^2+\left(2x+1\right)\left(3x-5\right)-2x\left(3-x\rig...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

17 tháng 8 2020

a) \(4x^2\left(5x^3-2x+3\right)\)

\(=20x^5-8x^3+12x^2\)

b) \(3y^2\left(4y^3+\frac{2}{3}y^2-\frac{1}{3}\right)\)

\(=12y^5+2y^4-y^2\)

c) \(\left(5x^2-4x\right)\left(x-2\right)\)

\(=5x^3-14x^2+8x\)

d) \(\left(3x-5\right)\left(2x+11\right)-\left(2x+3\right)\left(3x+7\right)\)

\(=6x^2+22x-55-6x^2-23x-21\)

\(=-x-76\)

17 tháng 8 2020

1, \(4x^2\left(5x^3-2x+3\right)=20x^5-8x^3+12x^2\)

2, \(3y^2\left(4y^3+\frac{2}{3}y^2-\frac{1}{3}\right)=12y^5+2y^4-y^2\)

3, \(\left(5x^2-4x\right)\left(x-2\right)=5x^3-10x^2-4x^2+8x=5x^3-14x^2+8x\)

4, \(\left(3x-5\right)\left(2x+11\right)-\left(2x+3\right)\left(3x+7\right)=6x^2+33x-10x-55-\left(6x^2+14x+9x+21\right)\)

\(=6x^2+23x-55-6x^2-23x-21=-76\)

7 tháng 9 2020

\(2x\left(2x-1\right)^2-3x\left(x+3\right)\left(x-3\right)-4x\left(x+1\right)^2\)

\(=x\left[2\left(2x-1\right)^2-3\left(x^2-9\right)-4\left(x+1\right)^2\right]\)

\(=x\left(8x^2-8x+1-3x^2+27-4x^2-8x-4\right)\)

\(=x\left(x^2-16x+28\right)=x\left(x-2\right)\left(x-14\right)\)

7 tháng 9 2020

\(2x\left(2x-1\right)^2-3x\left(x+3\right)\left(x-3\right)-4x\left(x+1\right)^2\)

\(=2x\left(4x^2-4x+1\right)-3x\left(x^2-9\right)-4x\left(x^2+2x+1\right)\)

\(=8x^3-8x^2+2x-3x^3+27x-4x^3-8x^2-4x\)

\(=x^3-16x^2+25x\)

20 tháng 4 2017

a) (x + 3)(x2 – 3x + 9) – (54 + x3) = (x + 3)(x2 – 3x + 32 ) - (54 + x3)

= x3 + 33 - (54 + x3)

= x3 + 27 - 54 - x3

= -27

b) (2x + y)(4x2 – 2xy + y2) – (2x – y)(4x2 + 2xy + y2)

= (2x + y)[(2x)2 – 2 . x . y + y2] – (2x – y)(2x)2 + 2 . x . y + y2]

= [(2x)3 + y3]- [(2x)3 - y3]


= (2x)3 + y3- (2x)3 + y3= 2y3

20 tháng 4 2017

Bài giải:

a) (x + 3)(x2 – 3x + 9) – (54 + x3) = (x + 3)(x2 – 3x + 32 ) - (54 + x3)

= x3 + 33 - (54 + x3)

= x3 + 27 - 54 - x3

= -27

b) (2x + y)(4x2 – 2xy + y2) – (2x – y)(4x2 + 2xy + y2)

= (2x + y)[(2x)2 – 2 . x . y + y2] – (2x – y)(2x)2 + 2 . x . y + y2]

= [(2x)3 + y3]- [(2x)3 - y3]

= (2x)3 + y3- (2x)3 + y3= 2y3

\(3x^4-4x^3+2x\left(x^3-2x^2+7x\right)\)

\(=3x^4-4x^3+2x^4-4x^3+14x^2\)

\(=5x^4-8x^3+14x^2\)

3x4 - 4x3 + 2x(x3 - 2x2 + 7x )

= 3x4 - 4x3 + 2x4 _ 4x3 + 14x2

= 5x4 - 8x3 + 14x2

12 tháng 6 2018

a)\(9x^2+30x+25+9x^2-30x+25-\left(9x^2-2^2\right)\)

=\(9x^2+54\)=\(9\left(x^2+6\right)\)

b)\(2x\left(4x^2-4x+1\right)-3x\left(x^2-9\right)-4x\left(x^2+2x+1\right)\)

=\(8x^3-8x^2+2x-3x^3+27x-4x^3-8x^2-4x\)

=\(x^3-16x^2+25x\)

c)\(\left(x+y-z\right)^2-2\left(x+y-z\right)\left(x+y\right)+\left(x+y\right)^2\)

=\(\left(x+y-z-\left(x+y\right)\right)^2\)=\(\left(-z\right)^2\)

29 tháng 9 2018

\(\left(x^2-1\right)\left(x+2\right)-\left(x-4\right)\left(x^2+4x+16\right)\)

\(=x^3+2x^2-x-2-\left(x^3-4^3\right)\)

\(=x^3+2x^2-x-2-x^3+64\)

\(=2x^2-x+62\)

\(2x\left(3x-2\right)^2\)

\(=2x\left(9x^2-12x+4\right)\)

\(=18x^3-24x^2+8x\)

\(\left(x-3\right)\left(x^2-3x+9\right)\)

\(=x^3-3x^2+9x-3x^2+9x-27\)

\(=x^3-3x^2+18x-27\)

29 tháng 9 2018

\(\left(x^2-1\right)\left(x+2\right)-\left(x-4\right)\left(x^2+4x+16\right)\)

\(=\left(x^2-1^2\right)\left(x+2\right)-x^3-4^3\)

\(=\left(x+1\right)\left(x-1\right)\left(x+2\right)-x^3-64\)

1: \(=x^3-6x^2+12x-8-8x^3-36x^2-54x-27+7\left(x-1\right)^3\)

\(=-7x^3-42x^2-42x-35+7x^3-21x^2+21x-7\)

\(=-63x^2-21x-42\)

2: \(=x^3+125-\left(x^3-8\right)=125+8=133\)

3: \(=8x^3-27-8x^3-12x^2-6x-1=-12x^2-6x-28\)

20 tháng 7 2017

1. \(\left(x+5\right)\left(x^2-5x+25\right)-\left(x-2\right)\left(x^2+2x+4\right)\)

\(=x^3+125-\left(x^3-8\right)=x^3+125-x^3+8=133\)

20 tháng 7 2017

1,

\(\left(x+5\right)\left(x^2-5x+25\right)-\left(x-2\right)\left(x^2+2x+4\right)\\ =\left(x^3+5^3\right)-\left(x^3-2^3\right)\\ =x^3+125-x^3+8\\ =\left(x^3-x^3\right)+\left(125+8\right)\\ =133\)

b,

\(\left(2x-3\right)\left(4x^2+6x+9\right)-\left(2x+1\right)^3\\ =\left[\left(2x\right)^3-3^3\right]-\left[\left(2x\right)^3+3\cdot\left(2x\right)^2\cdot1+3\cdot2x+1+1\right]\\ =\left(8x^3-27\right)-\left(8x^3+12x^2+6x+1\right)\\ =8x^3-27-8x^3-12x^2-6x-1\\ =\left(8x^3-8x^3\right)-\left(12x^2+6x\right)-\left(27+1\right)\\ =-6x\left(2x+1\right)-28\\ =\left(-2\right)\left[3x\left(2x+1\right)+14\right]\)